Incremental costs of prostate cancer trials: Are clinical trials really a burden on a public payer system? - Jones, Britney; Syme, Rachel; Eliasziw, Misha; Eigl, Bernhard J. (Canadian Urological Association Journal, 2013)
Introduction: Clinical trials are a critical component of improving cancer prevention and treatment strategies. However, the perception that patients enrolled in trials consume more resources than those receiving the standard-of-care (SOC) has contributed to an increasingly research-averse environment. Current economic data pertaining to the per-patient costs of prostate cancer trials relative to SOC treatment are limited. Methods: A retrospective observational cohort study was conducted to compare costs incurred by 59 prostate cancer patients participating in a mix of industry and non-industry sponsored clinical trials with costs incurred by an equal number of eligible nonparticipants who received SOC over a year. Resource utilization was tracked and quantified to standardized price templates. Results: No difference in overall resource utilization was seen between trial and SOC patients (two-tailed t-test, n = 118, p = 0.99). Variability in the types of resources used by each group indicated that, while trial patients may take up significantly more clinic time (p = 0.001) and undergo more tests and procedures (p = 0.001), SOC patients are more likely to receive other costly interventions, such as radiation therapy (p < 0.001). Other variables (e.g., pathology, diagnostic imaging, prescribed therapies) were statistically indistinguishable between groups. Conclusion: This study revealed differences in the cost distribution of patients enrolled in clinical trials versus those receiving SOC, which could be used to improve resource allocation. The lack of evidence for a difference in overall cost provides an argument for payers to more fully support clinical research without fear of adverse financial consequences. Further analysis is required.